Características clínico-epidemiológicas de pacientes adultos con dengue en Trujillo - Alcalde Loyola, Carlos César (2020)
The main objective of the present non-experimental research and descriptive retrospective design is to describe the clinical-epidemiological characteristics of adult patients with dengue in Trujillo. To this end, the clinical histories of patients with dengue treated at the MINSA level III hospitals of the city of Trujillo were reviewed. The data was recorded in a data collection matrix and the results were expressed as percentage values. It was found that 64% of patients were women, the average age was 35.5 years and the age group most affected was between 18-30 years (51%). The most common provenance was from the districts of El Porvenir (25.5%) and Florencia de Mora (20.6%). 91% of the cases were dengue with warning signs. The most common clinical and laboratory findings were headache (76.7%), thrombocytopenia (75.2%). The most frequent warning signs were: plaquetopenia (82.2%), abdominal pain (64.3%).